MEDICAL EXPULSIVE TREATMENT OF DISTAL URETERAL STONE USING TAMSULOSIN - Ahmad, Hussain; Azim, Waqar; Akmal, Muhammad; Murtaza, Badar; Mahmood, Arshad; Nadim, Amir; Shahzad, Khubaib (Journal of Ayub Medical College Abbottabad, 2015)
Background: Many minimally invasive interventional techniques as well as expectant treatments exist for the management of lower ureteric calculi. This study was conducted to evaluate the efficacy of tamsulosin as an expulsive pharmacologic therapy for the treatment of distal ureteral stone. Methods: This randomized control trial included 100 patients over 18 years of age with stone Size ‰¤8mm in distal 1/3 of ureter. Patients were randomly assigned into two groups (A & B). Group A Patients were given Capsule Tamsulosin 0.4 mg, 1 daily up to 4 weeks while group B patients were given placebo, 1 Capsule daily up to 4 weeks. The primary endpoint was expulsion rate. A written informed consent was taken from all the patients. Expulsion time, need for analgesics, need for hospitalization and drug side effects were secondary endpoints. Results: A total of 49 patients in group A and 48 patients in group B reported back, therefore 97 out of 100 patients were evaluated. Mean age of the patients was 36.34 years (range 18-57 years). Mean stone size was 5.78 mm (range 4-8 mm) in greatest dimension. A stone expulsion rate of 85.71% (42 patients) was noted in group A and 54.20% (26 patients) in group B. Group A revealed a statistically significant advantage in term of stone expulsion rate (p=0.032). Considering expulsion time in days group A showed statistically significant advantage (p=0.015). Regarding age, sex, stone size and stone lateralization (right/left), there was no significant difference between the group A and B. No drug side effects were noted in both the groups. Conclusion: By using tamsulosin a higher stone expulsion rates can be achieved in a shorter time. More randomized control trials are required to establish tamsulosin as a standard medical expulsive treatment for small distal ureteric calculus. Keywords: Tamsulosin, expulsive pharmacologic therapy, ureteral stone